The Relationship between Situational Leadership, Digital Transformation, and Adversity Quotient with the Performance of Vocational High School Teachers - Pane, Yenni Khairani; Darwin, Darwin; Rahman, Arif (Borong Newinera Publisher, 2024)
This study examines the interrelationships among situational leadership, digital transformation, adversity quotient (AQ), and teacher performance in Vocational High Schools (SMK) in Deli Serdang. The research involved 130 teachers, with a sample of 30 teachers selected through stratified random sampling. Data were collected using validated questionnaires measuring situational leadership, digital transformation readiness, AQ, and perceived teacher performance. The findings reveal significant positive correlations and predictive relationships among these variables. Situational leadership, aligned with Hersey and Blanchard’s theory, demonstrates its effectiveness in adapting leadership styles to meet teachers' varying needs and competencies. Digital transformation emerges as a strong predictor of teacher performance, emphasizing the importance of integrating technology into educational practices to enhance engagement and learning outcomes. Moreover, teachers with higher AQ exhibit greater resilience and adaptive capabilities, positively influencing their performance in managing classroom challenges and maintaining motivation amidst professional pressures. These findings underscore the importance of adaptive leadership, technological integration, and resilience building in fostering a supportive environment for teacher development and educational excellence. Practical implications highlight the need for leadership training programs that emphasize adaptive approaches, comprehensive strategies for digital integration, and resilience-building initiatives to support teachers’ professional growth. Future research could explore longitudinal impacts and qualitative dimensions to further enrich understanding of how these factors contribute to sustained teacher effectiveness and student achievement.